2012
DOI: 10.3390/molecules171214336
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antioxidant Activities of Three Red Wine Polyphenols and Their Mixtures: An Interaction Study

Abstract: The well-known antioxidant activity of red wine is explained mostly by its polyphenols content, where the final effect is based on the wine components’ interaction. The aim of our work was the study of the interaction of three red wine polyphenols—quercetin, resveratrol and caffeic acid—alone and in their equimolar binary and ternary mixtures in different antioxidant/scavenging assays (inhibition of 2-deoxy-D-ribose degradation by hydroxyl radical, FRAP, Fe(III) reducing power, DPPH, ABTS and NO scavenging, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
52
2
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 32 publications
(35 reference statements)
2
52
2
2
Order By: Relevance
“…Further, Silva et al (21) have used ethanolic solution of DPPH· and as demonstrated by Sharma and Bhat (22) , DPPH· displayed better sensitivity in methanol than in ethanolic medium. Kurin et al (23) have reported the DPPH· value of quercetin as 4.36 µM which is much close to 5.82 µM as obtained for rutin in the current study. Quercetin has hydroxyl group at position C-3 and higher radical scavenging activity than its glycoside derivatives including rutin.…”
Section: Resultssupporting
confidence: 89%
“…Further, Silva et al (21) have used ethanolic solution of DPPH· and as demonstrated by Sharma and Bhat (22) , DPPH· displayed better sensitivity in methanol than in ethanolic medium. Kurin et al (23) have reported the DPPH· value of quercetin as 4.36 µM which is much close to 5.82 µM as obtained for rutin in the current study. Quercetin has hydroxyl group at position C-3 and higher radical scavenging activity than its glycoside derivatives including rutin.…”
Section: Resultssupporting
confidence: 89%
“…Resveratrol (trans-3,5,4 1 -trihydroxystilbene) is a kind of phytoalexin belonging to the stilbene family [1]. It is present in natural foods and beverages (e.g., in grapes and red wine) and is widely consumed [2,3]. It has been suggested that moderate drinking of red wine helps to prevent cardiovascular disease; resveratrol in red wine is believed to be the key molecule due to its inhibitory activities against platelet aggregation and oxidation of low-density lipoprotein (LDL) in blood [4].…”
Section: Introductionmentioning
confidence: 99%
“…The content of caffeic acid in grapes can be as high as 70 mg L −1 (Makhotkina and Kilmartin, 2010). Antioxidant activity of caffeic acid was established (Kurin et al, 2012).…”
Section: Introductionmentioning
confidence: 99%